DESAIN ULANG BADAN JALAN DENGAN GEOTEKSTIL SEBAGAI ALTERNATIF PENINGKATAN STABILITAS LERENG - Rosiane Agustin; Handi Sudardja (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract The condition of Ciawi – Sukabumi Toll Road section 2 has various topographies with difference of elevation. To get a safe and comfortable road alignment, cut and fill works are carried out. During the landfill work at STA.18 + 700 – STA.18 + 900 landslides occurred on the slopes. To ensure that the slope conditions are safe during the service period, redesign of the road bodies is carried out to produce slopes with a safety factor value (SF) ≥ 1.25 (Bowles, 1993) and SF ≥ 1.10 if the earthquake is calculated (SNI 8460: 2017). The slope stability phase is calculated on the original slope conditions by taking into account the potential for earthquakes at the research location. This analysis was carried out with manual calculations and the GeoStudio 2018 R2 sub program SLOPE/W, both calculations using the Simplified Bishop Method. The results of the sliding analysis obtained the original slope SF without considering the earthquake of 1.48 for manual calculations and 1.41 for SLOPE/W. Then the SF of the slopes with the effect of the earthquake is 0.79 with manual calculations and 0.82 with SLOPE/W, it is found that all conditions are basic sliding. The analysis showed that the earthquake had a significant impact on slope stability, with a decrease in slope SF of 44.23% and the slope was categorized as unstable. Then, it is recommended to add woven geotextile with a tensile strength of 200 kN and a river stone gabion counterweight. From the modeling in each condition that has been simulated, it is found that the countermeasures are Type III with slope SF 1.15 as a redesign. . Keywords: Bishop, Geotextile, Safety factor, SLOPE/W, Slope stability